Undead Past: What Drives Support for the Secessionist Goal of the Indigenous People of Biafra (IPOB) in Nigeria? - Daniel Tuki (Journal of Race, Ethnicity and Politics, 2024)
This study examined the effect of perceived ethnic marginalization, perception towards Nigerian democracy, and socioeconomic condition on support for secession among members of the Igbo ethnic group. Perceived ethnic marginalization and negative perceptions toward Nigerian democracy were found to positively correlate with support for secession. Socioeconomic condition was measured at the household and communal levels. The household measure had no effect on support for secession, but the communal measure did: socioeconomic condition at the communal level positively correlated with support for secession. Igbo ethnicity increased the likelihood of supporting secession, while belonging to the Hausa/Fulani and Yoruba ethnic groups reduced the likelihood of supporting secession.
Keywords: 320; Indigenous People of Biafra; IPOB; secession; horizontal inequalities; ethnic marginalization; Nigeria